THE STUDY OF WORD FORMATION PROCESSES IN THE LIST OF TERMS OF HONDA SPAREPART - HIDAYAT, RAHMAT (Jurnal Ilmiah Mahasiswa FIB, 2015)
Key Terms: Honda Beat PGM-FI, List of Honda Genuine Part Sparepart, Terms ofSparepart, Word Formation Processes. In this globalization era, language develops rapidly along with the development of technology. People produce new terms for naming their new inventions or products. These new terms passed series of word formation processes before they were used in daily life. One of the examples which can be found in the real life is terms of motorcycle sparepart. In this research, the writer analyzes the word formation processes of terms of Honda sparepart found in the list of Honda Genuine Part sparepart using Yule’s theory. The purposes of this research are to analyze the word formation processes and also to know the dominant type of word formation processes found in the list of sparepart.In this research, the writer uses document analysis as the research design since this research describes the word formation processes of terms of sparepart found in the list of Honda Genuine Part sparepart. Specifically, the writer chooses Honda Beat PGM-FI motorcycle as the object of the research because this is the most selling motorcycle in Indonesia in 2014. The data of this study are sparepart terms containing word formation processes found in the list of sparepart.Research results reveal that derivation is the dominant process in the forming of terms of Honda sparepart. There are 46 terms of sparepart which are categorized as derivation out of 64 total terms. There are other word formation types found, they are compounding with 9 terms, clipping with 5 terms, acronyms with 3 terms, and blending with only one term.The writer believes this research is useful for students, especially those who are interested in studying Morphology, and also as a reference and comparison for the next researcher who wants to conduct a research in the same topic.